Social activities and different intensities of physical activity among older adults in China: a population-based cohort study - Yang, Song; Zhang, Qi; Zhao, Anhui; Lyu, Dongye (Frontiers in Public Health, 2025)
IntroductionPopulation aging is an inevitable consequence of demographic transition and an important issue for human society in the 21st century. Physical activity is widely recognized as a critical factor for improving health, yet the specific impact of different intensities of physical activity on the health of older adults remains underexplored.MethodsThis study addresses this gap by analyzing data from the China Health and Retirement Longitudinal Survey (CHARLS), a nationally representative survey of a cohort of Chinese people (aged ≥45 years) from 150 counties or districts and 450 villages or urban communities across 28 provinces, who were selected by use of multistage stratified probability-proportionate-to-size sampling. The study employed a regression model aiming to analyse the effect of different intensities of physical activity on the health level of the elder adults.ResultsThe results demonstrate that physical activity at all intensity levels—high, moderate, and low—significantly improves the health of older adults, with correlation coefficients of −0.245 (p < 0.01), −0.080 (p < 0.05), and −0.077 (p < 0.10), respectively. Among these, high-intensity physical activity is the most effective in enhancing health outcomes. The result further identifies social activities as a mediating factor in this relationship. Moreover, high-intensity exercise proves to be more beneficial for older adults residing in rural areas compared to their urban counterparts.DiscussionThis study demonstrates that engagement in physical activity at all intensity levels—high, moderate, and low—substantially enhances the health of older adults, with high-intensity physical activity demonstrating the most significant impact on health outcomes. Furthermore, the research identifies social activities as a mediating factor in this relationship, highlighting the importance of social engagement in conjunction with physical activity. This suggests that interventions promoting both physical activity and social interaction can be particularly effective in improving the health and wellbeing of the ageing population.